Tożsamość narodowa jako zagadnienie konstytucyjne - Sobczak, Jacek (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
The concept of national identity and consciousness are sociological and political concepts. However, they are connected with normative acts, in particular in the Constitution. They involve the problem of national and ethnic minorities. The sense of national identity is associated with a sense of belonging to the nation. It applies to individuals, has the character of a personal right and is associated with identification with the national community. The material scope of national identity is difficult to determine. However, it contains access to widely understood cultural goods. However, first of all, art. 35 of the Constitution, referring to national minorities. He lists the freedom to preserve and develop his own language, to maintain customs and traditions and to develop his own culture, as well as the possibility of creating educational and cultural institutions that also serve to protect religious identity. In the light of the analyzed views of doctrine, jurisprudence and international standards, it seems that there is no doubt that the concept of a nation in the Polish constitution is not ethnic. Such an ethnic meaning may have the notion of a national minority.
Keywords: nation; European Convention on the Protection of Human Rights; Constitution of the Republic of Poland; Framework Convention; national and ethnic minority